1999
DOI: 10.1177/0310057x9902700205
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Deadspace during Normocapnic Ventilation under Anaesthesia

Abstract: Respiratory physiological deadspace (VDphys) during normocapnic ventilation under anaesthesia was studied in 253 patients scheduled for elective non-thoracic surgery. Subjects were ventilated with SERVO 900B ventilator using CO 2 analyser 930 (Siemens-Elema Sweden) to adjust minute volume sufficient to maintain end-tidal carbon dioxide fraction (F É CO 2) around 5.5kPa with normocapnic confirmation using arterial blood gas analysis. VDphys was calculated using Enghoff's modification of Bohr's equation. VDphys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Differences are partly explained by lower degrees of lung injury in our patients. Our data overlap with observations in anaesthetised, ventilated subjects without primary lung disease [40,41]. The small effect of PEEP on VD phys found in our study is fully explained by the effect on VD aw .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Differences are partly explained by lower degrees of lung injury in our patients. Our data overlap with observations in anaesthetised, ventilated subjects without primary lung disease [40,41]. The small effect of PEEP on VD phys found in our study is fully explained by the effect on VD aw .…”
Section: Discussionsupporting
confidence: 61%
“…At a PEEP of 15 cmH 2 O, the average plateau pressure was 36 cmH 2 O (range [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Average PaCO 2 varied between 44.3 and 45.0 mmHg at different PEEP levels ( Table 2).…”
Section: Ventilationmentioning
confidence: 99%
“…VD/VT values ranging from 0.35 to 0.38 were reported in pediatric perioperative patients (23,30,31). A study in adults reported that VD is proportional to weight, height, and body surface area (36). We would not expect significant variations of VD/VT in the first year of life, since both VD and VT increase with age.…”
Section: Discussionmentioning
confidence: 92%